Competitividade do setor siderúrgico o dilema custo versus diferenciação: estudo de caso da CSN - Companhia Siderúrgica Nacional - Paula, Sérgio Iunis Citrangulo de (2007)
In the current economy, with both the information speed and the hypercompetition among the companies, it is necessary to analyze and understand new strategic alternatives to place organizations into this new environment. The traditional trade-off cost vs. differentiation diffused by Porter (1986) needs to be reevaluated to fit to this new market reality and taking into consideration the complexity of some new emerging strategic deals. This dissertation addresses theories about the competitive strategy based on a case study of Companhia Siderúrgica Nacional (CSN). This strategic analysis is made based on Porter s (1986) model and using the Delta Model proposed by Hax & Wild II (2001), applied as an alternative to the Porter s one. From a review of the literature over both models and also from the CSN s case analysis, this study presents the possibility to excel on Porter s trade-off in the strategic formulation, going deeper in the actions, combining costs vs. differentiation, taken by the Company. Based on the identification and consideration of the decisions made by the top management of the company, which lead CSN to present competitive advantage and, during these last years of privatization, has been enabling economic returns over the competitors and the interest of many investors. This dissertation discuss the consistence and effectiveness on Porter s (1986) generic competitive strategy proposal, and that it is possible to go further on the proposed trade off and think about combined strategies